Book review: An introduction to Irish planning law / by Berna Grist. Dublin: Institute of Public Administration, 1999. - Convery, Frank J.; Grist, Berna (Economic & Social Studies, 2001)
This slim volume (93 pages) is a very lucidly written overview of the planning system in Ireland, directed at the non-specialist. It is of particular value for those who wish to understand the evolution of the planning system as we experience it today, and those who wish to know how to operate it today. It is interesting to observe how the policy system has evolved over time in response to various inadequacies. From an economics point of view, this can be interpreted as follows: the planning system allows various rent seekers to maximise their position at the expense of the public interest. This rent capture gradually becomes obvious to the public and those responsible for the design and operation of the system, and these opportunities are curtailed; the rent seekers search out new opportunities.
Keywords: Book review; Planning system; Ireland; Planning law